Pengaruh Model Pembelajaran Guided Discovery Learning Melalui Hands On Activity Dan Media Gambar Ditinjau Dari Motivasi Belajar Sains Terhadap Pemahaman Konsep Fungi Peserta Didik - Lidia Banila; Mieke Miarsyah; Diana Vivanti (JURNAL KAJIAN ISLAM MODERN, 2023)
The low level of conceptual understanding of fungi, we need an appropriate learning model to overcome them. This research is aimed to determine the effect of guided discovery learning with hands-on activity toward the concept understanding of fungi, with the moderator variable being science learning motivation. The subject of this study are students of X IPA in SMAN 1 Bojonggede totaling 124 students on January–Maret 2018. The research method used a quasi-experiment with a 2 x 2 factorial design model. The instruments used were tests of science learning motivation and fungi comprehension tests. Samples were taken using simple random sampling. Analysis of data used two-way ANOVA. Sampling with simple random sampling. Data analysis using two-way ANOVA. The results of the analysis show that: (1) There is an influence of understanding the concept of fungi after guided discovery learning through hands-on activity (2) There is an influence of science learning motivation on understanding the concept of fungi. (3) There is an interaction of guided discovery learning through hands-on activity and science learning motivation towards the concept understanding of fungi.